(untitled) (Research, Society and Development, 2021)
The study of the food system does not find an explanation only in the logic of production or nutritional needs. In this context, this article aimed to describe food systems, including food environments, seeking to understand their possible influences on food and nutrition security (FNS). This is a case study, of a descriptive character, with a qualitative approach, carried out in the district of Sussundenga in Mozambique. The design of the work was carried out by systematic observation with a field diary and a talking map, involving the communities of Sussundenga-headquarters, Munhinga and Chidowa, as a basis for an explanatory model of the interactions and influences between the various variables. The results show that the food system, in geophysical and environmental components, with emphasis on climate change, may be one of the components that can most affect the FNS of communities, including food environments. In turn, the analysis of food environments has shown that the environment on public roads may present greater risks to human health, especially to children, partly due to issues related to the exposure of food in poor hygienic conditions, susceptible to causing diseases transmitted with symptoms of dehydration due to vomiting and diarrhea, when food is consumed under the conditions in which it is marketed. Thus, strategies and actions are needed to improve food systems, emphasizing the population’s awareness and resilience, as well as the empowerment of women to improve food choices with a view to promoting health and preventing diseases, through quality. nutrition and food safety.